2021
DOI: 10.1101/2021.02.04.429738
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Type-I interferon signatures in SARS-CoV-2 infected Huh7 cells

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that causes Coronavirus disease 2019 (COVID-19) has caused a global health emergency. A key feature of COVID-19 is dysregulated interferon-response. Type-I interferon (IFN-I) is one of the earliest antiviral innate immune responses following viral infection and plays a significant role in the pathogenesis of SARS-CoV-2. In this study, using a proteomics-based approach, we identified that SARS-CoV-2 infection induces delayed and dysregulated IFN-I sig… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 45 publications
(53 reference statements)
2
16
0
Order By: Relevance
“…In another study by us, we have observed that in Huh7 cells SARS-CoV-2 can inhibit type-I IFN signaling early, and the dysregulation in this pathway is only observed at 48hpi (Chen et al, 2021), which correlates with moderate production of the virus. In spite of differences in the dynamics of the cellular response, type-I IFN pre-sensitization of the Caco2, Calu-3 (Shuai et al, 2020), and Huh7 (Chen et al, 2021) has been shown to effectively inhibit SARS-CoV-2 infection. In addition, many of the ISGs such as IFIT1, ISG15, and DDX58 were upregulated in all three cell lines (Figure 6).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In another study by us, we have observed that in Huh7 cells SARS-CoV-2 can inhibit type-I IFN signaling early, and the dysregulation in this pathway is only observed at 48hpi (Chen et al, 2021), which correlates with moderate production of the virus. In spite of differences in the dynamics of the cellular response, type-I IFN pre-sensitization of the Caco2, Calu-3 (Shuai et al, 2020), and Huh7 (Chen et al, 2021) has been shown to effectively inhibit SARS-CoV-2 infection. In addition, many of the ISGs such as IFIT1, ISG15, and DDX58 were upregulated in all three cell lines (Figure 6).…”
Section: Discussionmentioning
confidence: 84%
“…Previous proteomics-based studies have observed that SARS-CoV-2 causes global proteomic changes after 48hpi specifically in pathways related to ErbB, HIF-1, mTOR, and TNF signaling ; complement system and coagulation cascades (Tiwari et al, 2020); and interferon signaling (Chen et al, 2021). In order to understand the delayed changes in Huh7 cells (Huh7 48h ) compared with Calu-3 and Caco2 cells, we extracted the proteomics dataset from our earlier study .…”
Section: Proteomic Analysis Of the Cell Linesmentioning
confidence: 99%
“…SARS-CoV-S and SARS-CoV-2-S pseudoviruses did not infect the hepatocyte cell line, Huh-7. The heterogeneity in ACE2 expression in Huh-7 cell populations together with the widely varied characteristics of different laboratory-passaged Huh-7 lines may explain the discrepancy in the susceptibility of Huh-7 cells to native SARS-CoV-2 infection (13,3032). In contrast, MERS-CoV-S pseudovirus, which preferentially binds DPP4 as a receptor rather than ACE2 (16), showed a high level of infectivity in Huh-7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Huh7 cells have been reported to be permissive to viral replication 4,23,[26][27][28][29][30] . Recently, a proteomics-based approach found activation of the type I IFN system in Huh7 cells at 48 hours but not 24 hours postinfection 31 . This indicates a delayed IFN induction in Huh7 cells, potentially explaining our results obtained at the 24-hour timepoint.…”
Section: Discussionmentioning
confidence: 99%